Microdilution procedure for antifungal susceptibility testing of Paracoccidioides brasiliensis to amphotericin B and itraconazole - Takahagi-Nakaira, E. [UNESP]; Sugizaki, M. F. [UNESP]; Peracoli, M. T. S. [UNESP] (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2009)
In vitro tests employing microdilution to evaluate fungal susceptibility to antifungal drugs are already standardized for fermentative yeasts. However, studies on the susceptibility of dimorphic fungi such as Paracoccidioides brasiliensis employing this method are scarce. The present work introduced some modifications into antifungal susceptibility testing from the European Committee on Antimicrobial Susceptibility Testing (EUCAST), concerning broth medium and reading time, to determine minimal inhibitory concentration (MIC) of amphotericin B and itraconazole against Paracoccidioides brasiliensis. Yeast-like cells of P. brasiliensis (Pb18 strain) were tested for susceptibility to amphotericin B and itraconazole in RPMI 1640 medium, supplemented with 2% glucose and nitrogen source and incubated at 35 degrees C. The MIC of amphotericin B and itraconazole against Pb18 were respectively 0.25 mu g/mL and 0.002 mu g/mL. The results of minimal fungicidal concentration (MFC) showed that amphotericin B at 0.25 mu g/mL or higher concentrations displayed fungicidal activity against Pb18 while itraconazole at least 0.002 mu g/mL has a fungistatic effect on P. brasiliensis. In conclusion, our results showed that the method employed in the present study is reproducible and reliable for testing the susceptibility of P. brasiliensis to antifungal drugs.
Keywords: amphotericin B; itraconazole; P. brasiliensis; antifungal susceptibility